Assistance model and historiography in Argentina in the liberal modernity (Quinto Sol, 2017)
The study of social and economic growth and the distribution of wealth has acquired new importance in the state, political social and scientific agenda since the last decade of the 20th century. There is an increasing interest in social sciences and humanities scholars in the study of those topics and in the processes leading to change in social and economic development and a fairer distribution of wealth in order to get a closer understanding of the present and to help design future social policies. This paper aims at studying the above referred issues from a historiographical point of view and will try to enlighten the complex process of building a social state in Argentina. It will mainly focus on the study on the workings of non-state institutions, either secular or religious, which invested money to help unemployed poor people during the modern liberal period. It evaluates the role of the non-state social aid and its impact on the political, cultural and social life of the period.
Keywords: social affairs; patterns of social aid; historiography; civil society